-
I wonder, is your question a straight line x-2y-3=0? Otherwise, there will be a in the expression, but it will be much simpler, because it will become a straight line parallel to the x-axis. (I don't know if I can do it, I haven't tried it, and it seems that I can't do it).
So I'll do it with x-2y-3=0. Since it passes through points a and b, let the center of the circle be q(a,b), and the distance from q to a and b is equal, both of which are radius r, then the equation can be listed: (a-3) 2+(b-2) 2=(a-2) 2+(b-1) 2
After the parentheses on both sides are squared, you can get an equation: a+b=4( ) I don't know if it's right, because it's mentally arithmetic, hehe), because (a, b) the straight line x-2y-3=0, so you can list the equation: a-2b-3=0 ( ) can solve the inequality by , that is, get this point, and finally substitute it into the above equation, and solve r.
q:(11/3,1/3)r∧2=29/9
If you have (a, b) and r, you can find the equation for this circle.
-
It's x-2y-3=0, right?
i.e. x=2y+3
Let the center of the circle o(2a+3,a).
oa²=ob²=r²
i.e.: (2a+3-3) +a-2) =(2a+3-2) +a-1) =r
The solution yields a = 1 3 and r = 29 9
o(11/3,1/3)
x-11/3)²+y-1/3)²=29/9
-
The midpoint of ab c(1,1), the slope of ab.
Therefore, the slope of the perpendicular line in the peidou ab is -2
Therefore, the middle vertical line is changed to the core branch of the middle sensitive equation:
y-1=-2(x-1)
That is: 2x+y-3=0
Synoptic: x+2y=0
x=2y=-1
So the center of the circle is (2,-1).
r^2=3^2+1^2=10
The circular equation is: x-2) 2+(y+1) 2=10ps: use the perpendicular line of the string to pass through the center of the circle to find the center of the circle.
-
a(5,2),b(3,2), the oblique scale of the straight line ab is 2-2 5-3 =0, the vertical bisector of the straight line ab is perpendicular to the x-axis, and its equation is: x= 5+3 2 =4, and the linear line 2x-3y-3=0 is solved in conjunction with x=4, y= 5 3, that is, the center m coordinate of the circle is (4, 5 3), and the radius of the circle is r=|am|= 5-4 ) 2 +(2-5 ) 2 = 10 , then the equation for the round-style void is (x-4) 2 + (dust slip y- 5 3 ) 2 = 10
-
Solution: The center of the circle is on the straight line 3x-y-2 0.
Let the center of the circle m (m, 3m-2).
The circle crosses two points a(3,1) and b(-1,3).
AB midpoint n is (1,2), KAB -1 2
kmn=(3m-4)/(m-1)
Kab KMN -1, ie.
1 2) (3m-4) (m-1) -1, solution m 2, then 3m-2 split plexus vertical 4
Center m(2,4).
The radius of the circle is ma Zheng Sheng 10
The circular equation is (x-2) 2 (y-4) 2 10
-
This question is not difficult to do with a closed grip, but it requires basic knowledge.
-
Let the center of the circle be (2a+3,a).
then the distance from the center of the circle to the two points is equal.
So (2a+3-2) +a+3) = (2a+3+2) +a+5).
2a+1)²+a+3)²=(2a+5)²+a+5)²4a+1+6a+9=20a+25+10a+25-20a=40
a=-2 so the center of the circle is: (-1, -2).
Radius = (2a+1) +a+3) = 10 so the equation is: (x+1) +y+2) =10
-
The center c of the circle is in the line l: x-2y-3=0
Let the abscissa of the center of the circle be a, then its ordinate is (a-3) 2 The equation of the circle is (x-a) +y- (a-3) 2] =r Substituting the points a(2,-3) and b(-2,-5) gives (2-a) +3-(a-3) 2] =r (-2-a) +5-(a-3) 2] =r The two-formula simultaneous solution is obtained.
a=-1r²=10
The circular equation is (x+1) +y+2) =10
-
Let the center of the circle be (2a+3,a) and the radius be r, then the circle equation is:
x-2a-3) 2+(y-a) 2=r 2 then there is: (2-2a-3) 2+(-3-a) 2=r 2(-2-2a-3) 2+(-5-a) 2=r 2 solution: a=-2
r^2=10
Circular equation: (x+1) 2+(y+2) 2=10
-
Solution: Let the center of the circle c(a,b), then 2a-b=3, b=2a-3 The equation for the circle: (x-a) 2+(y-2a+3) 2=cx=3,y=-2; x=5 and y=2 are substituted respectively to obtain:
3-a)^2+(-2-2a+3)^2=c(5-a)^2+(2-2a+3)^2=c
Solution: a=-2, c=50, b=2a-3=-7 The equation for the circle: (x+2) 2+(y+7) 2=50
-
Let the center of the circle be (a,b) and the radius be r
Since the center of the circle is on 2x-y=3, b=2a-3 lets the equation for the circle be.
x-a)²+y-2a+3)²=r²
Since a and b are both on a circle, they both satisfy the equation of a circle
5-a)²+2-2a+3)²=r²①
3-a) +2-2a+3) =r - get:
5-a)²-3-a)²]5-2a)²-1-2a)²]=0
Using the squared difference formula, we get:
5-a-3+a)(5-a+3-a)+(5-2a-1+2a)(5-2a+1-2a)=0
The solution is a=2, and substituting b gives b=1
Substituting a=2 into the equation, we get r =10
Hence the equation for a circle is:
x-2)²+y-1)²=10
-
Let the coordinates of the center of the circle be (x,y).
With the characteristics of a circle, it can be seen that the distance from the center of the circle to any point on the circle is the radius, so (x-2) 2+(y+3) 2=(x+2) 2+(y+5) 2 gives 8x+4y+16=0
Coupled with x-2y-3=0.
The coordinates of the center of the circle are (-1, -2).
The equation for a circle is (x+1) 2+(y+2) 2=10
-
Solution: The slope of the straight line x-2y-3=0 is 1 2, then the slope of the straight line ab is -2 because a(2-3) and b (-2.).-5), the equation for the straight line ab is y=-2x-4
x=-1 y=-2 r²=10
The equation for the garden (x+1) +y+2) =10
-
Solution: Set: Center coordinates: (x0, y0).
Radius: r then there are: (x-x0) 2+(y-y0) 2=r 2 because: the center of the circle is in a straight line, then: y0=6*(x0)......Liang pants fierce.
And the circle passes through the point: (-2, -3) and the point: (2, -5) i.e. .
2-x0)^2+(-3-y0)^2=r^2……2-x0) 2+(-5-y0) socks 2=r 2......Lianli Oak Bridge, solution, x0=-1
y0=6*(-1)=-6
r= 10, i.e., (x+1) 2+(y+6) 2=10
-
If the circle passes AB, the center of the circle is on the perpendicular bisector of AB.
The midpoint of ab is c(1,3).
The slope of ab is (2-4) (3+1)=-1 2, so the slope of ab perpendicular bisector is -1 (-1 2)=2, so ab perpendicular bisector is y-3=2(x-1).
The center of the circle is again on the y-axis.
Then x=0, so y-3=-2
So the center of the circle d(0,1).
then r =|ad|=(-1-0) +1-4) =10, so x +(y-1) =10
-
If the circle passes AB, the center of the circle is on the perpendicular bisector of AB.
The midpoint of ab is c(1,3).
The slope of ab is (2-4) (3
So the slope of the ab perpendicular bisector is -1 (-1 2)=2, so the ab perpendicular bisector is y-3=2(x-1).
The center of the circle is again on the y-axis.
Then x=0, so y-3=-2
So the center of the circle d(0,1).
then r =|ad|=(-1-0)
So x(y-1)=10
Adopt the next ha, thank you.
-
The center of the circle is on the perpendicular line, ab:
y=-1/2x+7/2
The midpoint is (1,3).
So the mid-vertical line is y-3=2(x-1).
Find the intersection of the mid-perpendicular line and the y-axis.
i.e. x=0, then y=1
So the center of the circle is zhidao(0,1).
The radius is the distance from the center of the circle to a or b = root number 10
So the equation is x +(y-1) = 10
-
Let the center of the circle be (0,y), and get (0+1)zd178; +(y-4) =(0-3) +y-2) gives y=1
radius =(0-3) +y-2) =10
The equation is x +(y-1) = 10
Dear I found the Chinese lyrics ** dh2 bar.
we are the b >>>More
a^3+b^3=(a+b)(a^2+b^2-ab)a^5+b^5=(a+b)^5-5ab[2ab(a+b)+a^3+b^3] >>>More
The monotonic increase interval of the function y=sinx is (2k -1 2 , 2k +1 2 ), k is an integer, and the monotonic decrease interval is (2k +1 2 , 2k +3 2 ), and k is an integer. >>>More
Solution: Let the equation for the straight line be.
y=ax+b >>>More
2A square B - [2AB square - 2 (A square B + AB square)].
2a²b-2ab²+2a²b+2ab² >>>More